Dynamic object recognition and command detection for assisting blind people using image processing techniques - Tahsin, Labeba; Nuba, Nadia Ahlam; Sami, Mashiat ferdous; Afrin, Sabrina (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.